2012
DOI: 10.1371/journal.pone.0036343
|View full text |Cite
|
Sign up to set email alerts
|

Sodium Selenide Toxicity Is Mediated by O2-Dependent DNA Breaks

Abstract: Hydrogen selenide is a recurrent metabolite of selenium compounds. However, few experiments studied the direct link between this toxic agent and cell death. To address this question, we first screened a systematic collection of Saccharomyces cerevisiae haploid knockout strains for sensitivity to sodium selenide, a donor for hydrogen selenide (H2Se/HSe−/Se2−). Among the genes whose deletion caused hypresensitivity, homologous recombination and DNA damage checkpoint genes were over-represented, suggesting that D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 43 publications
1
54
0
Order By: Relevance
“…Therefore, the production of H 2 Se catalyzed by Cys3p could be at the origin of SeMet toxicity. S. cerevisiae whole genome analysis highlighted the importance of the DNA damage response and repair pathway in H 2 Se toxicity (13). In this study, several mutants hypersensitive to H 2 Se showed wild-type sensitivity to SeMet.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…Therefore, the production of H 2 Se catalyzed by Cys3p could be at the origin of SeMet toxicity. S. cerevisiae whole genome analysis highlighted the importance of the DNA damage response and repair pathway in H 2 Se toxicity (13). In this study, several mutants hypersensitive to H 2 Se showed wild-type sensitivity to SeMet.…”
Section: Discussionmentioning
confidence: 64%
“…We investigated this hypothesis by determining SeMet sensitivity of deletion strains known to be hypersensitive to sodium selenide. These strains were chosen to represent the three most important pathways for selenide resistance: DNA damage checkpoint (rad9), DNA double-strand break repair (rad52), and GSH-mediated oxidative stress response (glr1) (13). All these mutants hypersensitive to sodium selenide showed wild-type growth rates in the presence of SeMet, ruling out hydrogen selenide implication in SeMet toxicity.…”
Section: H 2 Se Production Is Not Involved In Semetmentioning
confidence: 99%
See 1 more Smart Citation
“…O À 2 formation by SeMet appears to occur via its metabolite CH 3 SeH (57), but a similar argument applies to this process with regard to the mechanism. A recent study using sodium selenide has reported HO formation in yeast cells and implicated this radical in oxidative stress and the toxicity of selenium compounds (58); this observation requires validation and mechanistic investigation.…”
Section: Pro-oxidant and Adverse Effects Of Selenium-containing Aminomentioning
confidence: 99%
“…Se-induced ROS generation caused DNA strand breaks followed by cell cycle arrest and apoptosis, leading to suppression of cancer growth (Peyroche et al, 2012;Tobe et al, 2015). Such antitumor mechanisms of Se were attributed to pro-oxidative effects of inorganic Se compounds, rather than antioxidative effects of organic Se compounds (Drake, 2006;Ramoutar and Brumaghim, 2010).…”
Section: Introductionmentioning
confidence: 99%